A Fractal-Based Compact Tunable Bandpass Filter with High Selectivity and Band Rejection - Fadhil, Areeg; Jasim Farhan, Malik; K. Ali, Jawad; Alsultani, Ameer (Journal of Engineering and Sustainable Development, 2025)
Fractal geometries have emerged as a promising approach for designing compact, tunable electronic components, particularly in microwave and radio-frequency circuits. This article presents a tunable filter for mobile communications that exploits a miniaturized open Ring Resonator, fabricated using the Minkowski fractal method. The fractal resulted in a 25.1% reduction in size, with an overall filter surface area of 51.84 mm2. The proposed filter was constructed on a Roger RO4003 substrate with a center frequency of 2.69 GHz, a bandwidth of 0.14 GHz, and a compact size of 0.137λg × 0.13λg. This frequency will shift according to a variable capacitor added to the resonator with a range of 2.22-2.56GHz. The insertion loss of the tuning states ranged from 0.38 to 0.58 dB, the return loss was 20.7-28.4 dB, and the fractional bandwidth was 2.25-4.6%. This proposed design shows promising performance with 7.7 GHz band rejection, high selectivity, and a compact size.